Initial experience with the cook formula balloon expandable stent in congenital heart disease. Issue 2 (26th May 2014) - Quandt, Daniel; Ramchandani, Bharat; Bhole, Vinay; Penford, Gemma; Mehta, Chetan; Dhillon, Rami; Stumper, Oliver
<x xml:space="preserve">Abstract</x> Introduction Balloon expandable stents are an integral part in the catheter treatment of congenital heart disease. In the growing child, stents require dilatation to greater diameters over time. The Cook Formula stent is a recent 316 stainless steel open‐cell design licensed for peripheral vascular work. Methods Following extensive ex vivo studies, 112 stents were implanted in 97 children [median age 3.9 (0.01–17.6) years; median weight 13.7 (2.4–62.8) kg] over a 27‐month (Oct 2011–Dec 2013) period. Results Bench testing revealed that there was no stent shortening for dilatation to nominal diameter and beyond. The 5 mm stents could be dilated up to 10 mm, and the 10 mm stents to 20 mm. Stents were implanted through 4–7F sheaths or guide catheters over appropriate wires. Stent tracking and delivery was excellent. Twenty‐three stents were implanted in the right ventricular outflow tract in Fallot‐type lesions, 53 for branch pulmonary artery stenosis (22 post cavopulmonary shunt/Fontan), 14 conduit stenosis, 13 Fontan fenestrations, 3 PDA in hybrid stage I Norwood, 5 in coarctation, and 1 for SVC obstruction. Sixty‐one stents (54%) were overdilated. There were no stent fractures. Radial strength was very good, whereas stent conformability was limited. Conclusions The Cook Formula stent is a premounted balloon‐expandable stent that can be significantly overdilated with virtually no shortening allowing for precise placement and minimal protrusion into adjacent vessels. The Formula stent is a very versatile addition to the range of stents for use in the catheter treatment of complex congenital heart disease in children. © 2014 Wiley Periodicals, Inc.